Preventive measures compliance on patients with mechanical ventilation in the Critical Care Unit at the Hospital Guillermo Almenara Irigoyen, 2016 - Medina Laura, Gladys (2018)
Objective: To determine preventive measures compliance on patients with mechanical ventilation in the Critical Care Unit at the Hospital Guillermo Almenara Irigoyen. Materials and Methods: Prospective observational study of longitudinal cut, the population was comprised of the patients that entered the Critical Care Unit. For convenience, a non-probabilistic sample was used, which was comprised of 50 patients who were studied during the months of June to November of 2016. Patients who passed away within 48 hours of admission were excluded. The instrument used was a verification list made up of a set of six preventive measures containing dichotomous type answers, with a reliability of 0.80 using the Richarson Kuder method. Results: 52% of the patients who average ≥ 60 years old, with a male predominance, the respiratory pathology constituted 60% of the cases, 58% of the patients had between 10 and 19 days of use of mechanical ventilation and 78% of the did not show pneumonia. The adequate handling of the airway, hand hygiene during the handling of the airways and head bedside elevation, showed 73.6% of compliance, while the evaluation and records of the necessity of sedoanalgesia showed 70.9% of compliance. Conclusions: in 54% of the studied patients the preventive measures were achieved.